Synthesis of Sulfur/Nitrogen‐Enriched Polyimide and Interlayer Application for Inverted Polymer:Nonfullerene Solar Cells. Issue 10 (18th June 2019) - Kim, Dohan; Seo, Jooyeok; Lee, Chulyeon; Lee, Sooyong; Kim, Hwajeong; Kim, Youngkyoo
Abstract : Herein, it is reported that sulfur/nitrogen‐enriched polyimide can act as a stable interlayer for inverted‐type polymer:nonfullerene solar cells because it improves the power conversion efficiency (PCE) and stability of the devices. The sulfur/nitrogen‐enriched polyimide (E‐PI) interlayers are prepared on the zinc oxide layers via the thermal imidization of corresponding films of soluble precursor polymer, poly( N ‐(2‐((carboxymethyl)(2‐((5‴‐methyl‐[2, 2″:5″, 2″:5″, 2‴‐quaterthiophen]‐5‐yl)amino)‐2‐oxoethyl)amino)ethyl)‐ N ‐(2‐(methylamino)‐2‐oxoethyl)glycine acid), which is synthesized from ethylenediaminetetraacetic dianhydride and 5, 5‴‐diamino‐2, 2″:5″, 2″:5″, 2‴‐quaterthiophene. The E‐PI films exhibit high glass transition temperature (≈204 °C) and broad optical absorption up to ≈1000 nm (absorption edge). Results show that the average PCE of polymer:nonfullerene solar cells is increased from 10.86% to 11.6% at the E‐PI thickness of 3 nm. In particular, the stability of polymer:nonfullerene solar cells is clearly improved by inserting the 3 nm‐thick E‐PI interlayers. Abstract : A sulfur/nitrogen‐enriched polyimide (E‐PI) with high glass transition temperature (>200 °C) is synthesized and introduced as an interlayer for inverted‐type polymer:nonfullerene solar cells. The 3 nm‐thick E‐PI interlayers result in the improved efficiency and stability of poly[(2, 6‐(4, 8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)‐benzo[1, 2‐b:4, 5‐b″]dithiophene))‐alt‐(5, 5‐(1″, 3″‐di‐2‐thienyl‐5″, 7″‐bis(2‐ethylhexyl)benzo[1″, 2″‐c:4″, 5″‐c″]dithiophene‐4, 8‐dione))] (PBDB‐T):3, 9‐bis(6‐methyl‐2‐methylene‐(3‐(1, 1‐dicyanomethylene)‐indanone))‐5, 5, 11, 11‐tetrakis(4‐hexylphenyl)‐dithieno[2, 3‐d:2″, 3″‐d″]‐s‐indaceno[1, 2‐b:5, 6‐b″]dithiophene) solar cells due to the increased work function (electron mobility) of zinc oxide electron‐collecting buffer layers.